PENGARUH MOTIVASI BERWIRAUSAHA DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA (I) PROGRAM STUDI ILMU ADMINISTRASI BISNIS FISIP ULM BANJARMASIN - Ghifari, Muhammad Reza Iqbal; Irwansyah, Irwansyah (Bisnis Smart, 2020)
Muhammad Reza Iqbal Ghifari, D1A215228, 2019, The Effect of Entrepreneurial Motivation and Family Environment on Entrepreneurial Interest in Students (i) Business Administration Study Program FISIP ULM Banjarmasin. Under the guidance of Irwansyah.Indonesia is one of the countries with the most population in the world. Along with the increasing population of Indonesia from year to year and changes that occur in the era of industrialization also cause problems therein. These problems include the number of job seekers, the majority of which have graduated graduates, while the availability of jobs has diminished, coupled with the entry of the Asean Economic Community (MEA), which is a challenge for graduates with a degree of unemployment. One way to minimize unemployment in Indonesia is by increasing employment. Job opportunities can be created by opening up one's own employment or entrepreneurship.This study aims to examine the effect of Entrepreneurial Motivation (X1) Family Environment (X2) Towards Entrepreneurial Interest (Y) on Students (i) Business Administration Study Program FISIP ULM Banjarmasin.The research approach used is a quantitative approach. From the entire population, samples taken were taken by 100 respondents withtechniques Proportional Random Sampling. Data collection using questionnaires, while data analysis using multiple linear regression with SPSS Version 25.0.The results of this study prove that Entrepreneurial Motivation (X1) haseffect a partially significanton Entrepreneurial Interest (Y) because t sig <0.05 or 0,000 with a large influence of 46 , 4% and the Family Environment (X2) have no significant effect partially on Entrepreneurial Interest (Y) because tig> 0.05 or 0.181 with a large influence of 12.5%. Entrepreneurial Motivation (X1) Family Environment (X2) has a significant simultaneous effect onInterest Entrepreneurial(Y) because t sig <0.05 or 0,000 with a large effect of 25.6% while the remaining 74.4% is influenced by other variables that are not examined in this study.